Learning by Vying in Automotive Fabrication in Engineering Education - Saichandu, P V N; Prasad, Kowdodi Siva (Journal of Engineering Education Transformations, 2025)
By visualizing and engaging with the problem where many students struggle, mechanical engineering principles like Heat Transfer and FEM are better comprehended. Participating in design and development problems at the student level is one such approach that aids the students in picturizing, comprehending, and understanding the concepts. Students participate in a variety of racing competitions, such as the creation of the Quad Bike, Baja Buggy, Formula Student, etc. The students can create teams, build, and develop cars, compete against other teams nationally and globally, and more by taking part in these tournaments. Additionally, it improves the student's capacity for teamwork, empowers them to take on mission-driven projects, and develops their managerial and leadership abilities. Students improve their ability to comprehend, visualize a variety of engineering ideas during the process